2020
DOI: 10.3390/toxins12030172
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Exposure and Related Diseases

Abstract: Mycotoxins are considered the most frequently occurring natural contaminants in the diet of humans and animals [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For instance, Xu et al found 100% positivity for DON, 68.7% for ZEA, and 99.5% for deoxynivalenol-3-glucoside (DON-3-G) among 370 wheat samples in Anhui Province, China [8]. Exposure to mycotoxins has been linked to various chronic diseases, including neurodegenerative issues, cardiovascular disease, chronic enteritis, and endemic diseases [9][10][11]. Acute mycotoxin poisoning can be fatal to both animals and humans [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Xu et al found 100% positivity for DON, 68.7% for ZEA, and 99.5% for deoxynivalenol-3-glucoside (DON-3-G) among 370 wheat samples in Anhui Province, China [8]. Exposure to mycotoxins has been linked to various chronic diseases, including neurodegenerative issues, cardiovascular disease, chronic enteritis, and endemic diseases [9][10][11]. Acute mycotoxin poisoning can be fatal to both animals and humans [12].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to mycotoxins has been linked to various chronic diseases, including neurodegenerative issues, cardiovascular disease, chronic enteritis, and endemic diseases [9][10][11]. Acute mycotoxin poisoning can be fatal to both animals and humans [12].…”
Section: Introductionmentioning
confidence: 99%
“…There exist various types of mycotoxins, with a atoxin (AFB), zearalenone (ZEN), ochratoxin (OTA), and deoxynivalenol (DON) being the most wellknown ones. These mycotoxins pose a serious threat to human and animal health (Assunção et al 2020;Patrícia et al 2021).…”
Section: Introductionmentioning
confidence: 99%